Pilot study of the Greek Interventional Geriatric Initiative to Prevent Cognitive Impairment and Disability in individuals with subjective cognitive decline: paving the way towards brain health clinics in Greece - Alexopoulos, Panagiotis; Felemegkas, Panagiotis; Arampatzi, Xanthi; Billis, Evdokia; Dimakopoulou, Eleni; Economou, Polychronis; Dimakopoulos, George A.; Exarchos, Themis P.; Frounta, Maria; Giannakopoulou, Parthenia; Kalaitzi, Kalliopi; Koula, Maria - Lamprini; et al. (Frontiers in Psychiatry, 2025)
The pilot phase of the Greek Interventional Geriatric Initiative to Prevent Cognitive Impairment and Disability (GINGER) aims to assess the feasibility of a multi-level dementia risk reduction intervention in individuals with subjective cognitive decline (SCD) over a six-month period. The study design incorporates a comprehensive set of trans-disciplinary assessments and interventions in multiple centers across Greece. Individuals 55 years or older with subjective cognitive complaints who do not fulfill criteria for either mild cognitive impairment or dementia are screened for dementia risk factors in the following domains: nutrition, physical activities, vision and hearing, vascular and metabolic parameters, anxiety and depressive symptoms, and insomnia. All GINGER participants receive a cognitive empowerment intervention. Using a precision medicine approach, they receive up to three additional domain-specific interventions based on their individual risk factor profiles. Changes in cognition, dementia risk factors, quality of life and other measures compared to baseline are assessed at three- and six months after the initiation of the intervention. The GINGER protocol was designed and is run by a multi-disciplinary team of dieticians, neurologists, psychiatrists, psychologists, and physiotherapists, while computer scientists oversee data management. The objectives of this pilot phase are (i) evaluation of the protocol’s feasibility, (ii) assessment of intervention effects on the individual risk domains targeted by the interventions, (iii) estimation of the overall effects of the intervention on cognitive function, dementia risk and quality of life. The GINGER findings will provide a solid foundation for paving the way towards a network of evidence-based brain health clinics in Greece.